Strategi Komunikasi Pemelajar Bahasa Indonesia bagi Penutur Asing Asal Filipina - Yeyen Purwiyanti; Sarwiji Suwandi; NFN Andayani (Ranah: Jurnal Kajian Bahasa, 2017)
This research aims to describe and explain the communication strategy used by BIPA students from Philippines during BIPA learning. This research is a study case using natural background. The researcher will describe and explain both verbal and non-verbal communication strategy used by BIPA students of UPT Bahasa UNS who come from Philippines. Data of this research are result of observation and interview note from BIPA students from Phillipines as well as BIPA teachers. The result of this research is communication strategy used by BIPA students from Philippines, which are equivallance, borrowing, dictionary, self-correction, prefix, role play, phrase, preposition, similar pronounciation and diction. Communication strategy that is dominantly used by BIPA students is borrowing English in the communication of targeted language. Targeted language in this research is Indonesian. Verbal and non-verbal communication strategy has benefit toward BIPA students to understand the on-going event. Moreover, it could bridge the gap between the students and the teachers, as well as among the students.  AbstrakPenelitian ini bertujuan untuk mendeskripsikan strategi komunikasi yang digunakan oleh pemelajar BIPA asal Filipina dalam pembelajaran BIPA. Penelitian ini merupakan penelitian studi kasus dengan menggunakan latar natural. Peneliti akan mendeskripsikan dan menjelaskan strategi komunikasi verbal dan nonverbal yang digunakan oleh pemelajar BIPA UPT Bahasa UNS yang berasal dari negara Filipina. Data penelitian ini berupa catatatan lapangan hasil observasi dan catatan lapangan hasil wawancara pemelajar BIPA yang berasal dari Filipina dan pengajar BIPA. Hasil dari penelitian ini adalah strategi komunikasi yang digunakan oleh pemelajar BIPA asal Filipina, yaitu ekuivalensi, peminjaman, kamus, koreksi diri, imbuhan, peragaan, frasa, preposisi, kemiripan lafal, dan diksi. Strategi komunikasi yang dominan digunakan adalah peminjaman bahasa Inggris dalam menggunakan komunikasi bahasa target dalam penelitian ini adalah bahasa Indonesia.